The Predictive Value of the Mother's Risk Factors in Formation of Fetal Developmental Delay - Maka Chigladze PhD student (SAGE Publishing, 2021)
The research aimed at studying the mother's social-hygienic and medical biological risk factors and determining their predictive value. The retrospective case-control study was conducted with 142 pregnant women participating in it. In the case group there were involved 92 mothers whose pregnancy was completed by the birth of a newborn baby suffering from the intrauterine growth restriction. The control group was made of 50 pregnant women, whose pregnancy was completed by the birth of a healthy neonate. The research resulted in specifying the risk factors of high priority: the low standards of living (OR 3.61), chronic stress (OR-3.06), sleeping disorder (OR-3.33) and poor nutrition (OR-3.81). As regards the coexisting pathology the following was revealed: endocrine pathology (OR-3.27), ischemic heart disease (OR-4.35), arterial hypertension (OR-6.47), iron deficiency anemia (OR-4.11), pathology of respiratory system (OR-3.42), chronic genital inflammatory and infectious processes. The preeclampsia (92%) and low amniotic fluid (89%) were detected to have the high predictive value. The awareness of risk factors allows us to employ the timely measures for the reduction of negative impact on the fetus and neonate.